NILAI MORAL DAN RELIGIUS DALAM NOVEL SANGKAKALA DI LANGIT ANDALUSIA SERTA PEMANFAATANNYA SEBAGAI BAHAN AJAR DI SMA - Suandi; Hendri Henrian Algadri; Trisnawati (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to analyze the moral and religious values contained in the novel Sangkakala di Langit Andalusia by Hanum Salsabiela Rais and Rangga Almahendra and to examine their potential utilization as teaching material in senior high school. The research is motivated by the decreasing awareness of moral and religious values among students, which is considered a crucial challenge in the development of education and character building in Indonesia. Using a qualitative descriptive method, this research applies content analysis to identify, classify, and interpret moral and religious values represented in the narrative of the novel. The findings reveal that the novel embodies significant moral values such as honesty, responsibility, respect, empathy, and social care, as well as religious values including faith, worship, ihsan, knowledge, and righteous deeds. These values are presented both through the historical storyline of Muslim struggles in Andalusia and the contemporary journey of the authors, providing readers with lessons on identity, spirituality, and resilience. The discussion indicates that the integration of these values into teaching materials is relevant to the objectives of Indonesian language and literature learning in senior high schools, particularly in character education. The conclusion emphasizes that the novel can serve as an effective literary resource not only for improving students’ literacy skills but also for shaping their moral and religious character, thereby contributing to holistic education.